Effect of whey protein‐ and carbohydrate‐enriched diet on glycogen resynthesis during the first 48 h after a soccer game. Issue 4 (23rd November 2011) - Gunnarsson, T. P.; Bendiksen, M.; Bischoff, R.; Christensen, P. M.; Lesivig, B.; Madsen, K.; Stephens, F.; Greenhaff, P.; Krustrup, P.; Bangsbo, J.
Abstract : The effect of a whey protein‐ and carbohydrate (CHO)‐enriched diet on the rate of muscle glycogen resynthesis after a soccer match was examined. Sixteen elite soccer players were randomly assigned to a group ingesting a diet rich in carbohydrates and whey protein [CHO, protein, and fat content was 71, 21, and 8E%, respectively; high content of carbohydrates and whey protein (HCP), n  = 9] or a group ingesting a normal diet (55, 18, and 26E%; control [CON], n  = 7) during a 48‐h recovery period after a soccer match. CON and three additional players carried out a 90‐ and 60‐min simulated match without body contacts (SIM90 and SIM60). Muscle glycogen was lowered ( P  < 0.05) by 54, 48, 53, and 38% after the matches in CON, HCP, SIM90, and SIM60, respectively. Glycogen resynthesis during the first 48 h after the match was not different between CON and HCP, whereas glycogen resynthesis was slower ( P  < 0.05) during the first 24 h after SIM60 than SIM90 (2.88 ± 0.84 vs 4.32 ± 0.54 mmol/kg dw/h). In HCP, glycogen content in type II muscle fibers was still lowered 48 h after the match. In conclusion, glycogen resynthesis 48 h after a soccer match is not elevated by ingestion of a HCP diet. Furthermore, glycogen resynthesis does not appear to be impaired by body contacts during a match.